Synthesis of Silver‐Based Plasmas by Plant Extracts for In Vitro PTT/PDT/CT Synergistic Antitumor Therapy. (15th November 2022) - Xie, Yiliang; Dong, Baowen; Zhang, Xuan; Fan, Jimin; Lin, Jianying; Zhang, Bing; Zhao, Zhihuan
Abstract: In this study, biosynthetic Ag@AgCl plasma is used as a photosensitizer for the first time to construct a photothermal/photodynamic/chemotherapy and pH‐responsive synergistic antitumor nanomedicine delivery system CS‐Ag@AgCl/C. The Ag@AgCl and AgNPs synthesized by the extracts of alpine banana, C itrus reticulata, and Citrus sinensis are characterized. The Ag@AgCl NPs synthesized with banana extract have a regular crystal shape and a granular size of 12 nm, and they are more stable than AgNPs synthesized with the other two extracts. In addition, Ag@AgCl plasma used as a photosensitizer can reduce the dependence of CS‐Ag@AgCl/C on oxygen in the photodynamic process. After coating with chitosan, though the photothermal conversion efficiency of CS‐Ag@AgCl/C decreases from 44.06% to 29.51%, the pH response character of it increases, and the pH response plays an important role in drug release experiments. Under an acidic environment of pH = 5.0 phosphate‐buffered saline buffer, the drug release rate of the samples increases significantly. In the synergistic antitumor experiment, the cell survival rate increases from 36.83% to 78.69% after chitosan‐coated Ag@AgCl/C NPs. When CS‐Ag@AgCl/C‐DOX+808 nm is co‐cultured with HeLa cells, the cell survival rate is only 14.89%, which indicates that the constructed plasma drug delivery system has excellent photothermal/photodynamic/chemotherapy combined treatment capability. Abstract : A pH‐responsive drug delivery system (CS‐Ag@AgCl/C) is constructed using biosynthesized Ag@AgCl plasma as a photosensitizer, hollow carbon nanoparticles as a carrier, and chitosan as a shell. Doxorubicin shedding from chitosan is induced by a slightly acidic tumor site; under the irradiation of 808 nm laser, the temperature of nanoparticles increases while producing reactive oxygen species, realizing the combination of photothermal, photodynamic, and chemotherapy.